Human dental pulp stem cells transplantation combined with treadmill training in rats after traumatic spinal cord injury - Nicola,F.C. (2016)
Spinal cord injury (SCI) is a disabling condition resulting in deficits of sensory and motor functions, and has no effective treatment. Considering that protocols with stem cell transplantation and treadmill training have shown promising results, the present study evaluated the effectiveness of stem cells from human exfoliated deciduous teeth (SHEDs) transplantation combined with treadmill training in rats with experimental spinal cord injury. Fifty-four Wistar rats were spinalized using NYU impactor. The rats were randomly distributed into 5 groups: Sham (laminectomy with no SCI, n=10); SCI (laminectomy followed by SCI, n=12); SHEDs (SCI treated with SHEDs, n=11); TT (SCI treated with treadmill training, n=11); SHEDs+TT (SCI treated with SHEDs and treadmill training; n=10). Treatment with SHEDs alone or in combination with treadmill training promoted functional recovery, reaching scores of 15 and 14, respectively, in the BBB scale, being different from the SCI group, which reached 11. SHEDs treatment was able to reduce the cystic cavity area and glial scar, increase neurofilament. Treadmill training alone had no functional effectiveness or tissue effects. In a second experiment, the SHEDs transplantation reduced the TNF-α levels in the cord tissue measured 6 h after the injury. Contrary to our hypothesis, treadmill training either alone or in combination, caused no functional improvement. However, SHEDs showed to be neuroprotective, by the reduction of TNF-α levels, the cystic cavity and the glial scar associated with the improvement of motor function after SCI. These results provide evidence that grafted SHEDs might be an effective therapy to spinal cord lesions, with possible anti-inflammatory action.